P32 Gut sterilisation with norfloxacin modulates cerebral inflammation in cirrhosis and prevents deterioration in brain oedema and delays coma in cirrhotic rats. (16th November 2010) - Shah, N; Dhar, D; Mookerjee, R P; Davies, N A; Jalan, R
Abstract : Introduction: In a bile duct ligated (BDL) rodent model of cirrhosis, superimposed infection/inflammation leads to multiorgan failure including cerebral inflammation, worsening oedema and coma. The mechanism of why cirrhotic animals are predisposed to the effect of LPS is not clear. Toll like receptors, the ubiquitous receptors for bacteria trigger an inflammatory cascade through NFkB. We hypothesised that endotoxemia in cirrhosis primes the brain leading to an activation of TLR4 pathway which can be modulated by selective gut decontamination. Aim: The aims of the study were to determine whether (1) cirrhosis is associated with altered expression of TLR4 (endotoxin receptor), NFkB and cytokines in the brain and whether (2) selective decontamination of gut with norfloxacin would attenuate TLR4 expression and therefore protect against the development of accelerated brain oedema following LPS administration. Method: Six groups of Sprague–Dawley rats were studied (n=6 each). Animals underwent sham operation or bile-duct ligation (BDL) and were studied 4 weeks later. The animals were studied at coma stages after administration of LPS (1 mg/Kg) or vehicle. Study groups: Sham operated, Sham-operated+LPS; BDL (4 weeks), BDL+LPS; BDL+norfloxacin and BDL+LPS (norfloxacin 20 mg/kg daily for 10 days; PO). Ammonia (measured spectrophotometrically), brain cytokines (ELISA) were measured. Protein expression of Brain TLR4 and NFkBp65 was assessed with Western blot and the frontal cortex for brain water (dry weight method). Results: TLR4 and NFkBp65 protein expression was significantly higher in BDL rats (p=0.04 and p=0.03), this increased further on administration of LPS (p=0.02 and p=0.01) respectively. Norfloxacin reduced the expression of TLR4 and NFkBp65 to sham levels (p=0.03, p=0.02) respectively. Selective decontamination of gut with norfloxacin led to a reduction in ammonia (p=0.04, p=0.01), brain water (p=0.04, p=0.04) and brain TNF (p=0.02, p=0.02) in BDL and BDL rats treated with LPS respectively. Pre-treatment of the BDL animals with norfloxacin prior to administration of LPS significantly delayed occurrence of coma and improved survival (p<0.002). Conclusion: Our data provide strong evidence indicating an important pathogenic role of TLR4 in mediating susceptibility of cirrhotics to worsening coma following an infection/inflammation. Selective gut decontamination with norfloxacin attenuates the TLR4 expression thereby modulating the inflammatory milieu in the brain, delays coma and improves survival in cirrhotic animals administered LPS. Selective inhibition of TLR4 and/or selective gut decontamination may be therapeutic targets in hepatic encephalopathy.